Pendidikan Gender Berbasis Sastra - Teguh Trianton (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Recently, gender mainstreaming became most actual issue. One of its domains is on education. Practically, gender offered as important aspect on educational curriculum. From this point, emerge gender education discourse, namely an internalization process of gender equality issues through formal education. There are three important points on gender mainstreaming issue; first, gender education, two, gender issue on literary works, and three gender educations based on literary works.